Identification of factors that influence the delivery fee pricing of on-demand delivery services - De Oliveira, Leise Kelli; Mello, Carine Aragão de; Carneiro, Cheyenne Mariana de Oliveira; Costa, Tatiane Eugênia Remígio da; Araújo, Gracielle Gonçalves Ferreira de; Maia, Maria Leonor Alves (Frontiers in Future Transportation, 2022)
The use of on-demand delivery services increased in Brazil during the COVID-19 pandemic, mainly by requests for ready meals. While consumers appreciate convenience, the delivery fee is a decisive factor in the purchase process. However, the delivery fee pricing strategy of on-demand delivery service platforms has not been discussed in the literature. Thus, this study aims to analyze the factors that influence the delivery fee pricing of on-demand delivery services and explores the impact of delivery fee strategies on the remuneration of couriers. We collected data from three leading on-demand delivery service platforms regarding product type, order price, service fee, delivery fee, order day, order time, waiting time, and distance. As a result, our database comprises 1,440 orders in 12 Brazilian municipalities. A linear regression model was estimated to identify the factors influencing the delivery fee pricing considering different product types. Findings showed that product type has a diverse effect on delivery fee pricing. Moreover, distance, regardless of the product type, positively influences the delivery fee. The delivery fee of the ready meals is affected by the service fee, waiting time, order day, and order time. Furthermore, the waiting time and order day affect the delivery fee of supermarket and bakery products and beverages. Finally, the delivery fee of medical products is influenced by order day and time. Findings can be helpful for the pricing strategy of on-demand delivery services.